Revisiting the Homoploid Hybrid Speciation Process of the Triatoma brasiliensis macromelasoma Galvao, 1956 (Hemiptera, Triatominae) Using Cytogenetic and Molecular Markers - Guerra, Ana Leticia [UNESP]; Borsatto, Kelly Cristine [UNESP]; Damiano Teixeira, Nicolle Pagliusi [UNESP]; Madeira, Fernanda Fernandez [UNESP]; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Vilela Azeredo-Oliveira, Maria Tercilia [UNESP]; Chaboli Alevi, Kaio Cesar [UNESP] (Amer Soc Trop Med & Hygiene, 2019)
Triatomines are vectors of Trypanosoma cruzi, the etiologic agent of Chagas disease. Although the evolutionary process in triatomine is considered as disruptive, cryptic speciation and homoploid hybridization also are possible modes of speciation. Several analyses suggested Triatoma brasiliensis macromelasoma as a product of hybridization between T. brasiliensis and Triatoma juazeirensis. Thus, we analyzed genetic characteristics (chromosomal analysis, genetic distance for the mitochondrial ND1 gene, and the pattern of bands of internal transcribed spacer [ITS]-1) of these species, with emphasis on the phenomenon of homoploid hybridization. All species showed the same cytogenetic characteristics, low genetic distance for ND1 gene, and the same pattern of ITS-1 bands. We consider that these genetic characteristics, together with the large chromatic polymorphism and the viability of experimental crosses possibly are due to the processes of introgression that these species suffered during the process of homoploid hybridization.